2011
DOI: 10.1021/jp205963k
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Ground- and Excited-State Photophysical Properties of 5,10,15,20-Tetra(4-pyridyl)-21H,23H-porphyrin with Ruthenium Outlying Complexes

Abstract: The present work employs a set of complementary techniques to investigate the influence of outlying Ru(II) groups on the ground- and excited-state photophysical properties of free-base tetrapyridyl porphyrin (H(2)TPyP). Single pulse and pulse train Z-scan techniques used in association with laser flash photolysis, absorbance and fluorescence spectroscopy, and fluorescence decay measurements, allowed us to conclude that the presence of outlying Ru(II) groups causes significant changes on both electronic structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(21 citation statements)
references
References 46 publications
2
19
0
Order By: Relevance
“…The electron-transfer rate constant associated with the oxidative quenching of the S 1 state cannot be determined because the native lifetime of the ZnP S 1 state in the absence of quenching is unknown. Assuming that the native lifetime for this subunit is that of ZnTPP (τ 0 = 1.7 ns in CH 2 Cl 2 ), and using τ S1 = 900 ps reported by Casanova et al, the overall rate constant for the processes that accelerate S 1 decay can be estimated using eq to be k q = 5.2 × 10 8 s –1 . This contains contributions from the heavy-atom effect (or other nonradiative processes facilitated by the Re center) and oxidative quenching. As will be developed later based on data for 1 , the quantum yield and rate constant for oxidative quenching may be estimated to be ∼0.002 and 1 × 10 6 s –1 , respectively, with these small values being consistent with the fact that the electron-transfer reaction is roughly thermoneutral (Δ G ≈ −0.05 V) and occurs between weakly coupled redox orbitals (ZnPor and bpy).…”
Section: Resultssupporting
confidence: 68%
“…The electron-transfer rate constant associated with the oxidative quenching of the S 1 state cannot be determined because the native lifetime of the ZnP S 1 state in the absence of quenching is unknown. Assuming that the native lifetime for this subunit is that of ZnTPP (τ 0 = 1.7 ns in CH 2 Cl 2 ), and using τ S1 = 900 ps reported by Casanova et al, the overall rate constant for the processes that accelerate S 1 decay can be estimated using eq to be k q = 5.2 × 10 8 s –1 . This contains contributions from the heavy-atom effect (or other nonradiative processes facilitated by the Re center) and oxidative quenching. As will be developed later based on data for 1 , the quantum yield and rate constant for oxidative quenching may be estimated to be ∼0.002 and 1 × 10 6 s –1 , respectively, with these small values being consistent with the fact that the electron-transfer reaction is roughly thermoneutral (Δ G ≈ −0.05 V) and occurs between weakly coupled redox orbitals (ZnPor and bpy).…”
Section: Resultssupporting
confidence: 68%
“…The bond distances and angles listed in the caption of the Fig. 2 4-methylpyridine and 4-phenylpyridine, as previously reported [33,39,43,44]. In all three complexes, the dissociated chloride was always the one trans to a phosphorus atom in the precursor cis-[RuCl 2 (P-P)(bipy)] or cis-[RuCl 2 (P-P)(5,5 0 -Me-bipy)] {where P-P = aromatic biphosphine}, as expected, given the stronger trans effect of the phosphorus atom and in accordance with the X-ray structures.…”
Section: Syntheses and Non-covalent Interaction Between Aunps And Rutsupporting
confidence: 54%
“…The photodetector electrical signal was acquired by a 1 GHz oscilloscope and recorded by a computer. The procedure of measuring the sample fluorescence induced by pulse train is referred as pulse train fluorescence technique (PTF) [22], while the one using a single pulse is referred as time-resolved fluorescence technique (TRF).…”
Section: Experimental Set-upmentioning
confidence: 99%
“…For example, Gonçalves et al [20] demonstrated that the insertion of zinc in sulfonated porphyrin free-bases drastically reduced the ISC rate from 13 ns [21] to 2.2 ns [20]. Sampaio et al [22] have shown that free-base 5,10,15,20-tetra(4-pyridyl)porphyrin (H 2 TP y P) with ruthenium(II) ions bound at the peripheral groups of the macrocycle increases the ISC time about twofolds compared to porphyrins without Ru(II) (from 14 ns to 25 ns). This behavior is opposite to that of porphyrins with Ru(II) inserted in macrocycle core.…”
Section: Introductionmentioning
confidence: 99%